Program Layanan PAUD Non Formal dalam Mendukung Anak Jalanan Mengentaskan Pendidikan Wajib Belajar 9 Tahun - Malik, Halim K. (Jurnal Pelangi Ilmu, 2008)
Existence of road children still be considered to be town waste which must be removed. Improvement of number of child of roads is social phenomenon requiring attention from various party(sides. Child Of Road has good other childlike equal right of development of physical, bounces, social and personality that they have premising future. But child of road doesn\'t obtain its(the rights, even often its(the rights is often is impinged. Therefore needs existence of handling program child of road. Road children is victim either as victim in family, road community, and development victim. For the purpose protection campaign to child of road need to be done continually at least to push party( sides outside child of road to stop hardness actions to child of road.